(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study investigates the factors affecting Barangay Public Safety Officers (BPSOs) in responding to emergencies, with a particular focus on the influence of community participation and individual commitment. A major challenge identified is the lack of manpower, largely due to declining interest and willingness among individuals to continue volunteering. This shortage significantly hinders the ability of BPSOs to effectively respond to emergencies. The research aims to highlight the difficulties BPSOs face while balancing their responsibilities with personal struggles. By doing so, the study seeks to encourage potential volunteers—those aspiring to serve their communities or seeking renewed purpose through helping others—to consider becoming BPSOs in their barangays. As communities face increasing incidents of crime and natural disasters, the limited number of uniformed police officers is not sufficient to respond to all emergencies. This highlights the urgent need for additional support through committed volunteer manpower to enhance community safety and preparedness. This chapter presents the research design, the profile of the study’s respondents, the sampling technique employed, the research instrument used, the process of instrument validation, the procedures for administering and retrieving the instrument, and the statistical methods applied for data analysis. The findings present the age distribution of respondents in Barangay Commonwealth, Quezon City. The largest group of respondents was aged 42 to 49, ranking first with a frequency of 19, representing 38% of the total. Ranked second were those aged 26 to 33, with 11 respondents (22%). The third highest group consisted of individuals aged 50 and above, with a frequency of 9 (18%). Respondents aged 34 to 41 ranked fourth, totaling 6 individuals (12%). Lastly, the age group 18 to 25 ranked fifth, with 5 respondents, accounting for 10% of the total. The overall sample size was 50, representing 100% of the respondents. This chapter presents the summary and conclusions of the study, which focused on identifying the challenges and influencing factors affecting Barangay Public Safety Officers (BPSOs) in responding to emergencies in Barangay Commonwealth, Quezon City. It also offers recommendations for both residents and barangay officials to address these issues and strengthen emergency response efforts within the community.